Pengaruh Terapi Air Rebusan Daun Belimbing Wuluh Terhadap Penurunan Kadar Gula Darah di Wilayah Kerja Puskesmas Simalingkar Tahun 2022 - M. Rizky Ma’ruf; Mikha Lamtiur Sihaloho; Gusti Susanti Telaumbanua; Ayu Darman Halawa; Syukur Selamat Waruwu; Karmila Br Kaban (PT FORMOSA CENDEKIA GLOBAL, 2022)
The analysis in this study aims to determine the effect of water therapy boiled starfruit leaves on respondents who experience hyperglycemia in the working area of ​​the Simalingkar Health Center.. The design in this study uses the design pre-experiment (one group pre-test and post-test design). Researchers used a rational sampling , namely non-random sampling technique with a population of around 32 people. The sample of this study was an age range of 35-65 years with diabetes mellitus and not taking pharmacological therapy or blood sugar-lowering drugs in the working area of ​​the Simalingkar Public Health Center in 2022. The study was carried out on March 18, 2022 – March 25, 2022. From the results obtained, there was an effect of water therapy boiled with starfruit leaves on blood glucose levels in the working area of ​​the Simalingkar Health Center in 2022.